Prudent debt targets and fiscal frameworks - Fall, Falilou (OECD Publishing, 2015)
The sharp rise in debt experienced by most OECD countries raises questions about debt indicators and the prudent government debt level countries should target. It also raises questions about the fiscal frameworks needed to reach the prudent debt level and to accommodate cyclical fluctuations along the convergence path towards a prudent debt target. The objective of this paper is to define long-run prudent debt targets for OECD countries and country-specific fiscal rules. The paper presents a comprehensive analysis of government liabilities and assets and formulates recommendations for debt indicators. It also reviews the different linkages between government debt and the economic activity. The lessons from these analyses are combined with an assessment of the uncertainties surrounding the development of macroeconomic variables to define a prudent debt target. Different fiscal rules are compared with regard their impact on fiscal discipline and the risk of recession for country-specific fiscal rules recommendations
Keywords: Economics